2015
DOI: 10.1111/jocs.12609
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Synovial Sarcoma: A Rare Clinical Entity

Abstract: Synovial sarcoma is an extremely rare form of primary malignancy of the pericardium. We present a case of primary synovial sarcoma of the pericardium followed by a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…4 They tend to arise from the heart, mostly from the right atrium, but may also arise from the pericardium, as in our patient, with less than 25 cases described in the literature. 2,3 Almost all reported cases presented with exertional dyspnea and signs of cardiac tamponade from pericardial effusion. The only case that presented with angina was reported by Goldblatt and colleagues, 2 which was an incidental finding during coronary artery bypass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 They tend to arise from the heart, mostly from the right atrium, but may also arise from the pericardium, as in our patient, with less than 25 cases described in the literature. 2,3 Almost all reported cases presented with exertional dyspnea and signs of cardiac tamponade from pericardial effusion. The only case that presented with angina was reported by Goldblatt and colleagues, 2 which was an incidental finding during coronary artery bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial synovial sarcoma is a rare malignant tumor of the heart, with only 25 cases reported in the literature. 1,2 Most patients present with progressive dyspnea associated with pericardial effusion. We describe an unusual presentation of pericardial synovial sarcoma with unstable angina secondary to extrinsic tumor compression.…”
Section: Introductionmentioning
confidence: 99%
“…Для морфологической верификации показано выполнение биопсии новообразования перикарда. Для подтверждения диагноза первичной синовиальной саркомы перикарда проведение FISH-реакции является обязательным [14,15].…”
Section: краткие сообщения и заметки из практикиunclassified
“…Although the tumor image is nonspecific on the echocardiogram of an individual with pericardial synovial sarcoma, it is fundamental for the initial detection of the disease, quantification of the pericardial effusion, evaluation of cardiac function, and evaluation of cardiac restraint, as well as allowing comparative analysis with sequential follow-up examinations ( 10 ) . A solid, heterogeneous mass, with multilocular areas ( 11 ) and internal septa, is observed on CT and MRI; in some cases, there is invasion of adjacent structures, pericardial effusion and foci of metastases.…”
mentioning
confidence: 99%
“…A solid, heterogeneous mass, with multilocular areas ( 11 ) and internal septa, is observed on CT and MRI; in some cases, there is invasion of adjacent structures, pericardial effusion and foci of metastases. Cardiac MRI is considered the best modality for the detection and characterization of pericardial synovial sarcoma, because it makes it possible to observe the degree of vascularization, to better detail the cardiac invasion, and to monitor the post-treatment evolution ( 10 , 12 ) . In this context, it can be concluded that, although the imaging tests do not confirm the diagnosis, they play a fundamental role in the detection and characterization, as well as in the preoperative and postoperative planning, of pericardial synovial sarcoma.…”
mentioning
confidence: 99%